PENGARUH PENGALAMAN MAGANG DAN MOTIVASI KERJA TERHADAP KOMPETENSI PRAKTIS MAHASISWA AKHIR FAKULTAS EKONOMI - Ikbal Nurul Sodikin; Budiman; Intan Tenisia Prawita Sari (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to examine how experience during internships and motivation at work influence the development of practical skills possessed by final semester students at the Faculty of Economics, University of Garut. The approach used in this research is quantitative, with an associative research design, involving 74 respondents selected from a population of 277 students using the Slovin formula. Primary data were obtained through questionnaires, while secondary data were sourced from relevant scientific literature. Based on the results of the partial hypothesis test (t-test), the internship experience variable was found to have a significant influence on practical competence, as well as work motivation which was proven to make a positive contribution. Together, these two factors also have a positive impact on practical competence. A well-directed and structured internship experience is a key element in preparing students to fulfill their needs..